Children's literature in Hitler's Germany : the cultural policy of national socialism - Kamenetsky, Christa, 1934- (Ohio University Press, 1984)
Between 1933 and 1945, National Socialists enacted a focused effort to propagandize children's literature by distorting existing German values and traditions with the aim of creating a homogenous "folk community." A vast censorship committee in Berlin oversaw the publication, revision, and distribution of books and textbooks for young readers, exercising its control over library and bookstore content as well as over new manuscripts, so as to redirect the cultural consumption of the nation's children. In particular, the Nazis emphasized Nordic myths and legends with a focus on the fighting spirit of the saga heroes, their community loyalty, and a fierce spirit of revenge--elements that were then applied to the concepts of loyalty to and sacrifice for the Führer and the fatherland. They also tolerated select popular series, even though these were meant to be replaced by modern Hitler Youth camping stories. In this important book, first published in 1984 and now back in print, Christa Kamenetsky demonstrates how Nazis used children's literature to selectively shape a "Nordic Germanic" worldview that was intended to strengthen the German folk community, the Führer, and the fatherland by imposing a racial perspective on mankind. Their efforts corroded the last remnants of the Weimar Republic's liberal education, while promoting an enthusiastic following for Hitler.